PENGARUH PENAMBAHAN SARI BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KARAKTERISTIK YOGHURT CAMPURAN SUSU SAPI DAN KACANG MERAH (Phaseolus vulgaris) - Putri, Dewi Citra Laksmi Agung; Putra, I Nengah Kencana; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
The aim of this research was to know the effect of adding red dragon fruit juice (RDFJ) for the characteristics of yoghurt mixed milk and red bean. Research design used a randomized complete design (RAL) with the concentration 0 %, 5 %, 10 %, 15 %, 20 %, and 25 % of RDFJ. Each treatment repeated three times to obtain 18 units of sample. The data was analyzed by ANOVA and if it had effect on variabel then continued by Duncan Test. Sensory was analyzed by hedonic and scoring test for color, flavor, taste, texture and overall acceptance of the resulting product using 15 trained panelists. The result showed that adding RDFJ had very significant effects (P < 0,01) for total acid, Vitamin C, antioxidant activity, total lactic acid bacteria (BAL) and had significant effect (P < 0,05) for pH. The best treatment was on 15 % of RDFJ with value 1.22 % of total lactic acid, 4.41 of pH, 1.11 mg/100g of Vitamin C, 48.40 % of antioxidant activity, 1.87 x 10 8 CFU/ml of total lactic acid bacteria (BAL), color (red and liked), flavor (pleasant and liked), taste (sour and liked), texture (aqueous) and overall acceptance (liked).